SOSIALISASI TENTANG PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SDN 9 KABILA BONE, DI DESA OLUHUTA, KEC. KABILA BONE KAB. BONE BOLANGO - Yolanda Ngabito; Tiara Sahrain; Sri Ambar wati Malaiyo Malaiyo; Mawadda R Daud (Journal of Hulonthalo Service Society (JHSS), 2024)
The purpose of this community service is to increase the knowledge and awareness of elementary school children about the importance of implementing clean and healthy living behavior (PHBS). The implementation methods used in community service activities are; 1) problem identification; 2) formation of a proposing team; 3) observation of the activity location; 4) data collection; 5) identification of activity participants; 6) preparation of materials, facilities, and supporting infrastructure; 7) delivering materials; 8) development of local resources; 9) documentation; 10) reporting; and 11) publication. The results of this community service are that school children at SDN 9 Kabila Bone, Oluhuta Village, already understand the importance of implementing clean and healthy living behavior. The school and the Oluhuta Village community work together to be able to utilize knowledge about the socialization and training of how to wash hands properly and correctly (PHBS) for school children at SDN 9 Kabila Bone, Oluhuta Village.